Helminth Products Potently Modulate Experimental Autoimmune Encephalomyelitis by Downregulating Neuroinflammation and Promoting a Suppressive Microenvironment - Alberto N. Peón; Yadira Ledesma-Soto; Jonadab E. Olguín; Marcel Bautista-Donis; Edda Sciutto; Luis I. Terrazas (Mediators of Inflammation)
A negative correlation between the geographical distribution of autoimmune diseases and helminth infections has been largely associated in the last few years with a possible role for such type of parasites in the regulation of inflammatory diseases, suggesting new pathways for drug development. However, few helminth-derived immunomodulators have been tested in experimental autoimmune encephalomyelitis (EAE), an animal model of the human disease multiple sclerosis (MS). The immunomodulatory activities of Taenia crassiceps excreted/secreted products (TcES) that may suppress EAE development were sought for. Interestingly, it was discovered that TcES was able to suppress EAE development with more potency than dexamethasone; moreover, TcES treatment was still effective even when inoculated at later stages after the onset of EAE. Importantly, the TcES treatment was able to induce a range of Th2-type cytokines, while suppressing Th1 and Th17 responses. Both the polyclonal and the antigen-specific proliferative responses of lymphocytes were also inhibited in EAE-ill mice receiving TcES in association with a potent recruitment of suppressor cell populations. Peritoneal inoculation of TcES was able to direct the normal inflammatory cell traffic to the site of injection, thus modulating CNS infiltration, which may work along with Th2 immune polarization and lymphocyte activation impairment to downregulate EAE development.